Cork stoppers industry: defining appropriate mould colonization - Oliveira, A. C. (2010)
Aims: The main aims of this work were the study of cork slabs moulds colonization and the evaluation of the moulds diversity during cork processing steps, in different cork stoppers factories. Simultaneously, it was envisaged to perform an evaluation of the air quality. Methods and Results: Moulds were isolated and identified from cork slabs and cork samples in four cork stoppers factories. The identification was based on morphological characters and microscopic observation of the reproductive structures. Airborne spore dispersion was assessed using a two stage Andersen sampler. It was observed that Chrysonilia sitophila was always present on cork slabs during the maturing period, but mould diversity appeared to be associated to the different factory configurations and processing steps. Conclusions: Spatial separation of the different steps of the process, including physical separation of the maturation step, is essential to guarantee high air quality and appropriate cork slabs colonization, i.e. C. sitophila dominance. The sorting and cutting of the edges of cork slabs after boiling and before the maturing step is also recommended. Significance and Impact of the Study: This study is very important for the cork stopper industry as it gives clear indications on how to keep high quality manufacturing standards and how to avoid occupational health problems.